Achieving success and innovation in global sourcing : perspectives and practices : 9th Global Sourcing Workshop 2015, La Thuile, Italy, February 18-21, 2015, Revised selected papers /: perspectives and practices : 9th Global Sourcing Workshop 2015, La Thuile, Italy, February 18-21, 2015, Revised selected papers. (2015) - Unknown
No abstract available